2018
DOI: 10.1007/s10853-018-2799-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the core density on the quasi-static flexural and ballistic performance of fibre-composite skin/foam-core sandwich structures

Abstract: Polymeric foams are extensively used as the core materials in sandwich structures and the core material is typically bonded between relatively thin fibrecomposite skins. Such sandwich structures are widely used in the aerospace, marine and wind-energy industries. In the present work, various sandwich structures have been manufactured using glass-fibre-reinforced polymer (GFRP) skins with three layers of poly(vinyl chloride) foam to form the core, with the densities of the foam layers ranging from 60 to 100 kg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…, 1998), aerospace applications (Dangal et al ., 2021; Marx et al ., 2020) and automotive industry (Moon et al ., 2019; Romero et al ., 2021; Yavuz et al ., 2016). Porous structures can be used in ballistics for military areas (Ahmadi et al ., 2020; Kaboglu et al ., 2018; Marx et al ., 2019), shock absorbers and heat exchangers for vehicles (Chin et al ., 2022; Fiedler et al. , 2021; Kuruneru et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…, 1998), aerospace applications (Dangal et al ., 2021; Marx et al ., 2020) and automotive industry (Moon et al ., 2019; Romero et al ., 2021; Yavuz et al ., 2016). Porous structures can be used in ballistics for military areas (Ahmadi et al ., 2020; Kaboglu et al ., 2018; Marx et al ., 2019), shock absorbers and heat exchangers for vehicles (Chin et al ., 2022; Fiedler et al. , 2021; Kuruneru et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…There are many studies on the impact behavior and CAI behavior of sandwich composites at home and abroad. [5][6][7][8] Some researchers investigated the quasi-static indentation behavior of fiber reinforced with composite. Luo et al [9] studied the damage of composite materials in the quasi-static indentation and found that the specimen size and support conditions have little influence on the maximum load.…”
Section: Introductionmentioning
confidence: 99%
“…The quality of the molding process is evaluated based on the metallographic microstructures 37 . The lightweight foam core with various foam hybrid structures endows the core with a higher structure and function designability 38,39 . The development and applications of expandable foam have the ability for overcoming the molding challenges of various hybrid and reinforced sandwich composites 40,41 .…”
Section: Introductionmentioning
confidence: 99%
“…37 The lightweight foam core with various foam hybrid structures endows the core with a higher structure and function designability. 38,39 The development and applications of expandable foam have the ability for overcoming the molding challenges of various hybrid and reinforced sandwich composites. 40,41 Moreover, the epoxy foam will provide a better interface performance between the foam core and composite skin, and expand the application potential of sandwich composites.…”
mentioning
confidence: 99%